Mikrotik Login Security with Port-Knocking and Brute Force Firewall at PT. Time Excelindo - Iwan Giri Waluyo; Dedy Kurniawan (International Journal of Integrative Sciences, 2023)
In today's digital era, the use of MikroTik routers is increasingly common in companies, including PT Time Excelindo. However, attacks on MikroTik router logins are a frequent problem, and the company has a need to have a cheap and simple security system. This thesis aims to implement login security techniques using Port-Knocking and brute force firewalls on MikroTik routers at PT Time Excelindo, with the aim of providing solutions that are affordable and easy to implement. This study focuses on identifying the problems faced by PT Time Excelindo, namely repeated attacks against MikroTik router logins. The proposed solution involves implementing a Port- Knocking technique which will hide the login port on the router, so that only legitimate access will be allowed after a series of specific requests are made to certain ports. In addition, the firewall will also be activated to block brute force attacks by limiting the number of failed login attempts